Current impulse response of thin InP p[sup +]-i-n[sup +] diodes using full band structure Monte Carlo method - You, A. H.; Cheang, P. L. (AMER INST PHYSICS, 2007)
A random response time model to compute the statistics of the avalanche buildup time of double-carrier multiplication in avalanche photodiodes (APDs) using full band structure Monte Carlo (FBMC) method is discussed. The effect of feedback impact ionization process and the dead-space effect on random response time are included in order to simulate the speed of APD. The time response of InP p(+)-i-n(+) diodes with the multiplication region of 0.2 mu m is presented. Finally, the FBMC model is used to calculate the current impulse response of the thin InP p(+)-i-n(+) diodes with multiplication lengths of 0.05 and 0.2 mu m using Ramo's theorem [Proc. IRE 27, 584 (1939)]. The simulated current impulse response of the FBMC model is compared to the results simulated from a simple Monte Carlo model.(c) 2007 American Institute of Physics.